Does Vocabulary Breadth and Depth Predict Literary Comprehension? Evidence from Indonesia Grade-10 EFL Learners - Nur Diawati; Dihliza Basya; Fatih Alfauzi (Journey: Journal of English Language and Pedagogy, 2025)
This study investigates whether vocabulary breadth and depth predict literary comprehension among Indonesian Grade-10 learners of English as a foreign language (EFL), a domain that has received less attention than expository reading. Grounded in lexical and componential perspectives on reading, the study employed a quantitative correlational design. A total of 29 tenth-grade students completed a vocabulary proficiency test measuring breadth and depth, along with a short story comprehension test assessing literal and inferential understanding. Data were analyzed using Pearson product–moment correlation after meeting statistical assumptions. These findings suggest that while vocabulary proficiency contributes to literary understanding, it alone is insufficient to strongly predict comprehension of narrative texts. Literary reading appears to require additional cognitive and interpretive processes, such as inferencing and cultural interpretation, beyond lexical knowledge. The study highlights the importance of integrating vocabulary instruction with interpretive reading strategies when teaching literary texts in EFL contexts and provides a basis for further research with larger and more diverse samples.